Educational Service Marketing Methods in Increasing School Selling Value - M Masrur Huda; Mohammad Vauzi; Eni Erawati; Moh. Burhan (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2022)
This study's purpose was to determine the education marketing method at MINU Tenggulunan. This is descriptive qualitative research with data collection methods using observation, interviews and documentation. Data analysis uses several steps: reducing data, presenting data and verifying. The study results found that MINU Tenggulunan had implemented several suitable marketing methods for educational institutions to improve the school's image. This can be seen from the variety of marketing strategies used by educational institutions. This school has offered products that are in line with the community's needs, the fees charged to MINU Tenggulunan students are affordable compared to other private schools, and this school is in a strategic place to carry out educational activities. The marketing methods carried out by the MINU Tenggulunan institution are by conducting promotions through student guardians, printing media, social media and school output.